2015
DOI: 10.1007/s00216-015-8874-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of volatile organic gunshot residues in fired handgun cartridges by headspace sorptive extraction

Abstract: In forensic investigation of firearm-related cases, determination of the residual amount of volatile compounds remaining inside a cartridge could be useful in estimating the time since its discharge. Published approaches are based on following the decrease of selected target compounds as a function of time by using solid phase micro-extraction (SPME). Naphthalene as well as an unidentified decomposition product of nitrocellulose (referred to as "TEA2") are usually employed for this purpose. However, reliabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 38 publications
2
45
2
Order By: Relevance
“…This could include linking a person to such an event, an estimation of shooting distance and trajectory, bullet entry and exit point identification or simply determining the circumstances of a case and verifying the veracity of a testimony [1][2][3]. Additional information concerning the type of firearm and ammunition used as well as the time since discharge can also be useful [4][5][6][7]. GSR consists of a complex mixture of organic and inorganic material originating from the firearm, the ammunition and the combustion products formed during the discharge [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This could include linking a person to such an event, an estimation of shooting distance and trajectory, bullet entry and exit point identification or simply determining the circumstances of a case and verifying the veracity of a testimony [1][2][3]. Additional information concerning the type of firearm and ammunition used as well as the time since discharge can also be useful [4][5][6][7]. GSR consists of a complex mixture of organic and inorganic material originating from the firearm, the ammunition and the combustion products formed during the discharge [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The same storage conditions as those experienced by the questioned cartridges should be applied to reference material. The type of cartridges used as reference material should also be consistent, as previous research showed a dependence between GSR composition and ammunition [14]. Secondly, that knowledge about the environmental conditions at the crime scene before the questioned cartridges have been sampled should ideally be collected in order to correctly reproduce them in laboratory.…”
Section: General Discussion and Conclusionmentioning
confidence: 93%
“…Out of the 29 substances targeted with the developed method, 21 were chosen as predictors for training (Table S1). The three unaltered smokeless powder compounds (i.e., ethylcentralite, dibutyl phthalate and diphenylamine) were discarded because of low repeatability in their detected amounts [14]. Moreover, five explosion products (i.e., o-and m-tolunitrile, 1,3-and 1,4-dicyanobenzene, and isoquinoline) were also discarded due to co-elution issues compromising their detection and relative quantification (see part 1).…”
Section: Model Training and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…propellant powder) and combustion products [1]. There are over a hundred organic compounds with a possible association to GSR [1,2], many of which can be found in environmental and occupational materials [1,3]. A small selection of around twenty of these compounds have recently been highlighted as OGSR compounds that have a potential relevance to the confirmation of GSR materials [4].…”
Section: Introductionmentioning
confidence: 99%